2012
DOI: 10.1111/j.1468-2354.2012.00722.x
|View full text |Cite
|
Sign up to set email alerts
|

How Many Firms Should Be Leaders? Beneficial Concentration Revisited*

Abstract: This article investigates the relationship between the Herfindahl-Hirschman Index (HHI) and welfare in multipleleader Stackelberg models. We formulate two long-run models of free entry of followers; in the first (second) model, leaders select their output before (after) the entry of the followers. We find that in both models, in contrast to the short-run models, the Stackelberg model yields a larger welfare and HHI than the Cournot model does regardless of the number of leaders; that is, beneficial concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 32 publications
1
45
0
Order By: Relevance
“…5 4 Xu et al (2017) is one exception, as it discussed the timing of privatization, showing that earlier privatization is better for domestic and world social welfare in a specific model with linear demand and symmetric quadratic costs. Regarding the timing of commitment, Ino and Matsumura (2012) discussed two Stackelberg models in private oligopolies. In the strongly (weakly) persistent leadership model, Stackelberg leaders produce their outputs before (after) the entry of followers.…”
Section: Introductionmentioning
confidence: 99%
“…5 4 Xu et al (2017) is one exception, as it discussed the timing of privatization, showing that earlier privatization is better for domestic and world social welfare in a specific model with linear demand and symmetric quadratic costs. Regarding the timing of commitment, Ino and Matsumura (2012) discussed two Stackelberg models in private oligopolies. In the strongly (weakly) persistent leadership model, Stackelberg leaders produce their outputs before (after) the entry of followers.…”
Section: Introductionmentioning
confidence: 99%
“…This property is known in the literature on free-entry markets (see Etro, 2007;Ino and Matsumura, 2012).…”
Section: Equilibriummentioning
confidence: 94%
“…Ino and Matsumura (2012) showed that the existence of leaders always improves welfare in free-entry markets. However, in our model, an increase in r reduces total social surplus unless it reduces social costs, which are not discussed in this note.…”
Section: Lemmamentioning
confidence: 99%
See 1 more Smart Citation
“…3 In various contexts, contrasting implications are obtained in free-entry markets, and thus the literature on the analysis of free-entry markets in both private and mixed oligopolies is nascent. See Etro (2007), Ono (1995, 2007), Ino and Matsumura (2012), and Hattori and Yoshikawa (2016) for further details. 4 Privatization neutrality theorem states that privatization does not affect welfare regardless of time structure, competition mode, the number of firms, product differentiation, and the degree of privatization under the optimal output subsidy.…”
Section: Modelmentioning
confidence: 99%